Influência dos ajustes cardiorrespiratórios durante a respiração aérea do bagre africano (Clarias gariepinus) exposto à hipóxia - Teixeira, Mariana Teodoro [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Air-breathing fish occur mostly in tropical regions, especially in estuaries and freshwater lakes, where the amount of dissolved oxygen is highly susceptible to fluctuations. Thus, the ecological success of these animals is particularly influenced by their physiological adjustments to detect changes in O2 levels in the water, interpret sensory information and make appropriate adjustments in their cardiorespiratory functions. Almost all air-breathing fish studied to date exhibit changes in heart rate (fH) associated with surface air breathing . It is assumed that those cardiorespiratory adjustments facilitate O2 uptake from air-breathing organ (ABO) (increased cardiac output which increases blood flow) and optimize the distribution of O2 to the tissues, increasing the efficiency of air breathing and then aerobic metabolism is maintained. In this research the cardiorespiratory parameters (fH, gill breathing frequency- fR and frequency of air breathing - fRA ) were evaluated in Clarias gariepinus for 1 hour in normoxia and then hypoxia 60 mmHg and 1 hour 1 hour in hypoxia 20 mmHg. Each animal was first submitte to this protocol (CTR), and the same was repeated after administration of propranolol (PRO) and after administration of atropine (ATR + PRO) . The fR of CTR animals in normoxia was almost constant (~ 43.16 resp.min - 1) and the two hypoxic tensions (60 and 20 mmHg) also remained stable, however we detected no significant decrease when compared to normoxia. The propranolol and atropine did not cause significant changes in fR. In CTR fish in normoxia, fRA was reduced (~ 1.85 RA.h - 1), in hypoxia 60 mmHg there were a raising and this increase was higher in hypoxia 20 mmHg . The administration of propranolol + atropine significantly change fRA compared to control only during severe hypoxia (20 mmHg). In CTR animals, during normoxia and hypoxia (60 and 20 mmHg ), the occurrence of tachycardia was observed after the RA 's. The ...

Os peixes de respiração aérea ocorrem, em sua grande maioria, em regiões de clima tropical, principalmente em estuários e lagos de água doce, onde a quantidade de oxigênio dissolvido é bastante suscetível a oscilações. Dessa forma, o sucesso ecológico desses animais é particularmente influenciado pelas suas adaptações fisiológicas para detectar mudanças nos níveis de O2 da água, interpretar estas informações sensoriais e efetuar ajustes apropriados nas suas funções cardiorrespiratórias. Praticamente todas as espécies de peixe de respiração aérea estudadas apresentam alterações na frequência cardíaca (fH) associadas a respiração aérea (RA). Supõe-se que estes ajustes cardiorrespiratórios facilitem a captação de O2 no órgão de respiração aérea (ORA) (aumento do débito cardíaco que eleva o fluxo sanguineo) e otimize a distribuição desse O2 para os tecidos, aumentando a eficácia da respiração aérea e assim o metabolismo aeróbico é mantido. Nesse trabalho foram avaliados os parâmetros cardiorrespiratórios (fH, frequência de respiração branquial - fR e frequência de respiração aérea - fRA) de Clarias gariepinus durante 1 hora em normóxia e posteriormente 1 hora em hipóxia 60 mmHg e 1 hora em hipóxia 20 mmHg. Cada animal foi submetido a este protocolo inicialmente (CTR), e o mesmo era repetido após administração de propranolol (PRO) e após administração de atropina (PRO+ATR). A fR dos animais CTR em normóxia foi praticamente constante (~ 43,16 resp.min-1) e nas duas tensões hipóxicas (60 e 20 mmHg) também se manteve estável, entretanto foi verificada uma diminuição não significativa quando comparado a normóxia. O propranolol e a atropina não causaram alterações significativas na fR. Nos peixes CTR, em normóxia, a fRA foi reduzida (~1,85 RA.h-1), em hipóxia 60 mmHg houve uma elevação da fRA e esse aumento foi maior em hipóxia 20 mmHg. A administração de atropina ...
Keywords: Biologia; Peixe de agua doce; Bagre (Peixe); Hipóxia; Adaptação (Biologia); Freshwater fishes